The Effectiveness Of Using Multiple Intelligences Courseware In Learning Multimedia Subject - Mohd Salleh, Mohd Azran; Mohamad, Siti Nurul Mahfuzah (RMP Publications, 2017)
The theory of Multiple Intelligences (MI) was used in this paper. This courseware provides multiple learning approaches that can achieve community colleges mission to provide a systematic and integrated education and training. There are at least seven types of intelligences that human possess. Objective: The objective of this paper is to evaluate the effectiveness of learning using MI Courseware. Methodology: The methodology used is based on the ADDIE teaching model that consists of five phases. An evaluation of MI Courseware has been completed by 42 students from Kolej Komuniti Masjid Tanah. Results: The findings revealed those items related to the MI courseware contents produced good responses. The results showed that the MI Courseware can help and enhanced student’s skills in Community College. Conclusion: Overall, the perception of respondents towards the MI Courseware was encouraging.